THE EFFECT OF BTPN BANK CREDIT PROVISION ON THE WELFARE LEVEL OF TASPEN AND ASABRI PENSION CUSTOMERS - Inka Mariska Abriyana; Waloyo; Danang Apriliyanto; Siswohadi; Abdul Manan (CV Pena Jaya Pers, 2024)
This study aims to describe the effect of lending on the welfare of retirees and ASABRI. This research method uses quantitative methods, data collection techniques used are questionnaires. Bank BTPN KCP Magetan is a private bank that provides credit services for Taspen and Asabri retirees. The data analysis technique used is a simple linear regression technique. The results of this study are based on the results of simple linear regression testing, the value of the lending coefficient of 1.209 has a positive effect on the welfare of customers at Bank BTPN at KCP Magetan. Based on the results of the T test, it was obtained 0.000 so that the hypothesis was accepted. From the results of testing the coefficient of determination of the lending variable (X) has an effect of 77.7% on the customer welfare variable (Y) while the remaining 22.3% is influenced by other variables not examined by the researcher.